Crystal structures of Zn(cyclam)I2 (second monoclinic polymorph) and Zn(cyclam)I(I3) - Sergey P. Gavrish (International Union of Crystallography, 2021)
The asymmetric unit of the first title compound iodido(1,4,8,11-tetraazacyclotetradecane-κ4N1,N4,N8,N11)zinc(II) iodide, [ZnI(C10H24N4)]I, I, consists of the zinc–cyclam macrocyclic cation with one iodide anion coordinated to the metal ion [Zn—I = 2.6619 (5) Å] and the second present as a counter-ion. The asymmetric unit of the second title compound iodido(1,4,8,11-tetraazacyclotetradecane-κ4N1,N4,N8,N11)zinc(II) triiodide, [ZnI(C10H24N4)]I3, II, consists of half of the centrosymmetric macrocyclic cation, in which the ZnII ion coordinated to an iodide anion [Zn—I = 2.766 (2) Å] is disordered over two positions [Zn...Zn = 0.810 (3) Å], and of the two halves of the crystallographically non-equivalent, non-coordinated, centrosymmetric triiodide anions. In both compounds, the N,N,N,N-tetradentate macrocyclic ligand is present in the most energetically favored trans-III conformation. In the crystals of I, the [Zn(C10H24N4)I]+ cations and the non-coordinated iodide anions are linked by N—H...I and bifurcated N—H...(I,I) hydrogen bonds, resulting in the formation of two-dimensional networks lying parallel to the (001) and (101) planes. In contrast, the crystals of II are built up from infinite chains of the five-coordinate macrocyclic units arranged along the b-axis direction and perpendicular sheets formed of the triiodide counter-ions without significant hydrogen bonding between them.